Study the Effect of Addition of (Used Lubricating Oils: Polystyrene) and Air Blowing on the Rheological Properties of Asphalt - Ammar Ahmed Hamdoon (International Journal of Advanced Science and Technology, 2020)
In this study, the structural modifications for the commercial paving asphalt have been achieved. A mixture of wasted motors oils and polystyrene has utilized in the presence of an air oxidation process to improve the rheological properties of asphalt. The above mixture was added with different ratios ranging from 1-5% by weight under optimal conditions for the predetermined air oxidation process. The ductility, penetration and softening point of modified models were measured. Furthermore, the Marshal test was measured for the original model and the best-modified model obtained. A very high specification model was obtained based on the Marshal test which exceeded the commercial model in its quality.